Aksit Intervention (Prayer Activity, Study, Picket) in Optimizing Social Interaction in Children with Special Needs - Sari, Nurita; Zulfa, Nadia Aliyatuz; Setyo, Bono (PT. Hafasy Dwi Nawasena, 2025)
Children with special needs often face challenges in developing the social and emotional skills essential for healthy interactions in society. Various intervention approaches can be implemented to support their development, one of which is through the integration of structured and supportive activities. This study aims to examine the effectiveness of the AKSIT intervention in improving the social interaction of children with special needs in the Ainul Yakin Village, Gunung Kidul. The method used in this research is a qualitative approach with participatory observation, interviews, and documentation analysis. The AKSIT intervention involves three main components: (1) Sholat, which aims to develop children's discipline, cooperation, and spiritual calmness; (2) Kajian, which conveys social values such as empathy, responsibility, and cooperation; and (3) Piket, which involves children in household and cleaning tasks to increase their sense of responsibility and independence. The results showed that the integration of these three activities had a positive impact on improving children's social skills, including the ability to communicate, cooperate and build more harmonious relationships with peers and caregivers. The findings suggest that the AKSIT intervention can be an effective approach in developing the social and emotional skills of children with disabilities and facilitating their adaptation to wider social life. This study suggests the importance of continuing the AKSIT program in supporting the social development of children with disabilities in the cottage environment and the wider community.